Effect of seaweed fertilization and spraying with Tecamin Max on some qualitative traits of corn (Zea mays L.) - Sarour Khalid Samawi Al-Baazi (Journal of Kerbala for Agricultural Sciences, 2025)
A field experiment was carried out during the spring season of 2024 in the experimental fields of district Al-Husseiniya, Kerbala, Iraq, with the aim of studying the effect of soil fertilization with seaweed and spraying with the nutrient solution Tecamin Max on some growth and quality indicators of corn variety of 5018. The complete randomized block design was used according to the arrangement of factorial experiments with three replicates and two factors. The first factor included four concentrations of soil fertilization with seaweed, which are 0, 4, 8, and 12 kg ha-1, while the second factor included four different concentrations of foliar spraying with Tecamin Max, which are 0, 1, 2, 3 ml L-1. The results showed that the treatment of adding seaweed 12 kg h-1 was superior in giving the highest rate of the characteristics of nitrogen percentage, phosphorus percentage, potassium percentage, protein percentage, oil percentage, which reached (1.4533%, 0.555%, 0.4250%, 9.083%, 4.212%) respectively, compared to the comparison treatment which gave the lowest values. The results of foliar spraying with Tecamin Max compound showed that the level of 3 ml L-1 was superior in giving the highest rate for the same characteristics above which reached (1.4242%, 0.512%, 4.158%, 8.901%, 3.687%) respectively. Regarding the interaction between the study factors, the results showed no significant interactions, which means that the study factors behaved separately.